2007
DOI: 10.1111/j.1601-1546.2009.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Complications during root canal irrigation

Abstract: Although endodontic irrigants are generally considered to be safe, severe complications can occur during or as a consequence of root canal irrigation. However, no data on the incidence of irrigation incidents could be found. In the following paper, a review is presented on the possible incidents that may occur during root canal irrigation with different irrigation solutions, the sequelae, as well as prevention and therapy of such intra‐ and post‐operative problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
64
0
8

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(74 citation statements)
references
References 181 publications
(261 reference statements)
1
64
0
8
Order By: Relevance
“…During endodontic treatment, the irrigants can come in contact with the periradicular tissues, and in some instance they can create complications such as tissue damage and subsequent degrees of discomfort to the patient with possible interferences with the healing process (14). Therefore, it is important to select an irrigant with therapeutic benefits that could be weighed against its potential cytotoxic effects and to use a diluted concentration of the irrigant that still exhibits adequate antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During endodontic treatment, the irrigants can come in contact with the periradicular tissues, and in some instance they can create complications such as tissue damage and subsequent degrees of discomfort to the patient with possible interferences with the healing process (14). Therefore, it is important to select an irrigant with therapeutic benefits that could be weighed against its potential cytotoxic effects and to use a diluted concentration of the irrigant that still exhibits adequate antibacterial properties.…”
Section: Discussionmentioning
confidence: 99%
“…The data obtained showed that TAED+P may increase the effectiveness of the bleaching process in virtue to its ability to accelerate oxygen release from sodium perborate-distilled water mixtures (13). On these bases, the aim of this study is to test the cytotoxicity TAED+P on L929 fibroblasts and to compare it with that of NaOCl, which is still the ''gold standard'' for endodontic irrigation (9) despite its possible adverse effects (14). …”
mentioning
confidence: 99%
“…Both the extrusion of irrigation solutions and debris can irritate the periapical tissues and may cause interappointment emergencies (29). This leads to the controversial discussion regarding the impact of the creation of an apical (dentin) plug or of the patency approach on the incidence of flare-ups and the treatment outcome.…”
Section: Basic Research-technologymentioning
confidence: 99%
“…To increase the efficiency of syringe irrigation, different needle types have been proposed (7)(8)(9)(10)(11)(12)(13). Previous studies of the resulting flow (7,8,10,12) were limited because an indirect or a macroscopic approach can only provide a coarse and incomplete estimation of the irrigant flow.…”
mentioning
confidence: 99%